Sobre la distribucion de Asterodiaspis ilicicola (TARGIONI-TOZZETTI, 1888)(Homoptera, Asterolecaniidae) en encina - Soria, F.J.=700 1 Villagran, M.; Martin, P.; Ocete, M.E.
(Es, En)
ilus., 6 ref.
Keywords: HOMOPTERA; INSECTA; ASTEROLECANIIDAE; QUECUS ILEX; DISTRIBUCION GEOGRAFICA; ESPAÑA; ASTERODIASPIS ILICICOLA